Apolipoprotein A-I mimetic peptide helix number and helix linker influence potentially anti-atherogenic properties - Geoffrey D. Wool; Catherine A. Reardon; Godfrey S. Getz (Journal of Lipid Research, 2008)
We hypothesize that apolipoprotein A-I (apoA-I) mimetic peptides better mimicking the punctuated α-helical repeats of full-length apoA-I are more anti-inflammatory and anti-atherogenic. This study compares a monomeric apoA-I mimetic helix to three different tandem helix peptides in vitro: 4F (18 mer), 4F-proline-4F (37 mer, Pro), 4F-alanine-4F (37 mer, Ala), and 4F-KVEPLRA-4F [the human apoA-I 4/5 interhelical sequence (IHS), 43 mer]. All peptides cleared turbid lipid suspensions, with 4F being most effective. In contrast to lipid clearance, tandem peptides were more effective at remodeling mouse HDL. All four peptides displaced apoA-I and apoE from the HDL, leaving a larger particle containing apoA-II and peptide. Peptide-remodeled HDL particles show no deficit in ABCG1 cholesterol efflux despite the loss of the majority of apoA-I. Tandem peptides show greater ability to efflux cholesterol from lipid-loaded murine macrophages, compared with 4F. Although 4F inhibited oxidation of purified mouse LDL, the Ala tandem peptide increased oxidation. We compared several tandem 4F-based peptides with monomeric 4F in assays that correlated with suggested anti-inflammatory/anti-atherogenic pathways. Tandem 4F-based peptides, which better mimic full-length apoA-I, exceed monomeric 4F in HDL remodeling and cholesterol efflux but not LDL oxidation protection. In addition, apoA-I mimetic peptides may increase reverse cholesterol transport through both ABCA1 as well as ABCG1 pathways.